The universe of babassu coconut breakers - Lima, Vanusa da Silva; Nasuti, Stéphanie (Sustainability in Debate, 2017)
Palm forests, or babaçuais, designate geographical areas with large incidence of the babassu palm trees. This palm tree, from the botanical family Arecaceae, is native to Brazil, and can be found in several Latin American countries. In Brazil, babassu palm trees are present in 11 states (mainly in the states of Maranhão, Piauí, Tocantins and Pará) thus covering a territory of 13 to 18 million hectares . An anthropic forest par excellence, babassu palm trees tend to occupy areas which have been previously deforested by slash and burn clearing. Proliferation of the babassu is fast, as it can become a closed forest within a few years. Babassu extractivism is a traditional activity in Brazil due to its widespread coverage and countless uses in rural life, as well as the strong social and political mobilization in favor of free access to babassu forests.